Figurative Language In “Four” Album By One Direction : Semantic Analysis - Salsabila Kayla; Ervina Cm Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This research investigates figurative language in song lyrics, specifically focusing on One Direction's ‘Four’ album, to uncover deeper meanings and evoke emotional responses. Using a qualitative method, the research collected and analyzed data based on Johnson and Arp’s classification of figurative language, which consists of twelve types. The data were collected through careful listening and textual analysis of the album’s official lyrics, with findings cross-verified using multiple sources..The findings reveal a total of 66 instances of figurative language in the album, distributed as follows: irony (7 instances, 10.6%), personification (6 instances, 9.1%), symbol (17 instances, 25.75%), metaphor (23 instances, 34.84%), and hyperbole (13 instances, 19.7%). The results indicate that metaphor is the most frequently used type of figurative language in the album. This study highlights the role of popular music as a creative medium for literary expression and provides insight into how figurative language can enhance listener engagement. The findings may serve as a reference for educators and students in the fields of linguistics, literature, and music studies.